Bioestimulación de suelo contaminado con 60,000 ppm de aceite residual automotriz con detergente, extracto fúngico, H2O2, solución mineral y fitorremediación por Sorghum vulgare con Penicillium chrysogenum y Aspergillus niger - Saucedo Martínez, Blanca Celeste (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
Soil contaminated with 60,000 ppm of waste motor oil(WMO) is a hazardous waste (LEGEEPA, 2004) and exceeds the maximum concentration of 4,400 ppm according to NOM-138-SEMARNAT-SSAI-2012 (NOM-138) An alternative solution is the biostimulation (BIS) and phytoremediation (PHYTO). The hypothesis of the study was BIS of contaminated soil by 60,000 ppm of WMO with detergent (DEGE), H2O2, fungal extract crude (FUEX), mineral solution (MISO), soluble concentration of PO≡4 (phosphates) and humidity control at 80% and FITO using Sorghum vulgare inoculated with P. chrysogenum y A. niger at value below the maximum permitted by NOM-138. The aims of the work were: a) BIS of contaminated soil by 60,000 ppm of WMO with DEGE, H2O2, FUEX, MISO, soluble concentration of PO≡4 and humidity control at 80%. b) Identification of bacterial populations producing DEGE from soil with ARA. c) PHYTO using S. vulgare with P. chrysogenum and A. niger at value below the maximum permitted by NOM-138. The soil contaminated with WMO was treated by BIS and FITO, the residual WMO was quantified by Soxhlet, they were selected DEGE-producing bacterial populations in soil with WMO, phenology and biomass of S. vulgare were determined during PHYTO. Results showed that the BIS of soil which contains 60,000 ppm of WMO/8 weeks decreased to 32,700 ppm. Actinomycetes, firmicutes and proteobacteria DEGE-producing were identified. The subsequent PHYTO using S. vulgare with A. niger y P. chrysogenum decreased to 2,649 ppm value below the maximum permitted by NOM-138-SEMARNAT/SSA1-2012. This shows that the integration of the BIS and PHYTO of soil with relative high concentration of WMO is an effective remediation alternative.

La contaminación de suelo por 60,000 ppm de aceite residual automotriz (ARA) es un residuo peligroso (LEGEEPA, 2004) y excede la máxima concentración de 4,400 ppm según la NOM-138-SEMARNAT-SSAI-2012 (NOM-138). Una alternativa solución es la Bioestimulación (BIS) y fitorremediación (FITO). La hipótesis de la investigación fue que la BIS del suelo con 60,000 ppm de ARA con detergente (DEGE), H2O2, extracto fúngico crudo (EFUC), solución mineral (SOMI), PO≡4 (fosfatos) solubles y control de humedad a 80%, seguida de FITO por Sorghum. vulgare mediante Penicillium chrysogenum y Aspergillus niger reducirá el ARA a valor menor al máximo aceptado por la NOM-138. Los objetivos fueron: a) La BIS de suelo con 60,000 ppm de ARA, con DEGE, H2O2, EFUC, SOMI, PO≡4 soluble, control de humedad al 80%. b) Identificación de poblaciones bacterianas productoras de DEGE de suelo con ARA. c) FITO por S. vulgare con P. chrysogenum y A. niger para reducir el ARA a valor menor al máximo aceptado por la NOM-138. El suelo con ARA se bioestimulo y fitorrremedio, el ARA remanente se midio por Soxhlet, se seleccionaron poblaciones bacterianas productoras de detergente en suelo con ARA y determinación de la fenología y biomasa del S. vulgare en la FITO. Resultados mostraron que la BIS de suelo con 60,000 ppm de ARA/8 semanas lo disminuyó 32,700 ppm. Se identificaron actinomicetos, firmicutes y proteobacterias productores de DEGE y la FITO mediante S. vulgare con A. niger y P. chrysogenum lo redujo de 32,700 ppm a 2,649 ppm valor menor al máximo señalado por la NOM-138. Esto demuestra que la integración de BIS y FITO en suelo con relativa alta concentración de ARA fue efectiva para remediarlo.
Facultad de Biología. Facultad de Ingeniería Civil. Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Ambiental
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2016-1512; Detergente; Extracto fúngico; A. niger; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4748